2014
DOI: 10.1039/c4cy00289j
|View full text |Cite
|
Sign up to set email alerts
|

Ageing induced improvement of methane oxidation activity of Pd/YFeO3

Abstract: The ageing characteristics of flame-made 2 wt% Pd supported on YFeO 3 were analysed in comparison with a Pd/Al 2 O 3-CeO 2-ZrO 2 three-way catalyst (TWC) with respect to structural changes and catalytic performance for methane oxidation under stoichiometric reaction conditions. Thermal treatment under lean conditions (air, 900°C) resulted in slight decrease in the methane oxidation activity of the TWC. In marked contrast, YFeO 3-supported Pd catalysts exhibit an increase in activity after such treatment. Activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 93 publications
2
26
0
Order By: Relevance
“…Pd catalysts used for CH 4 oxidation are known to deactivate in the presence of H 2 O and the effect of H 2 O decreases with increased temperature, which is in agreement with the TOS and TPO results of this study. The structural collapse of the catalyst support, sintering and PdO conversion to Pd have all been stated as the reason for the deactivation of Pd catalysts . Kucharczyk et al studied the effect of adding La 2 O 3 and SiO 2 or ZrSiO 4 to the washcoat of a PdO/γ‐Al 2 O 3 catalyst and reported that these promoter oxides improved the activity and stability and enhanced the thermal resistance of the PdO/γ‐Al 2 O 3 catalysts after aging at 1060°C for 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Pd catalysts used for CH 4 oxidation are known to deactivate in the presence of H 2 O and the effect of H 2 O decreases with increased temperature, which is in agreement with the TOS and TPO results of this study. The structural collapse of the catalyst support, sintering and PdO conversion to Pd have all been stated as the reason for the deactivation of Pd catalysts . Kucharczyk et al studied the effect of adding La 2 O 3 and SiO 2 or ZrSiO 4 to the washcoat of a PdO/γ‐Al 2 O 3 catalyst and reported that these promoter oxides improved the activity and stability and enhanced the thermal resistance of the PdO/γ‐Al 2 O 3 catalysts after aging at 1060°C for 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…One is a Fourier analysis (FA) that gives unambiguous results if the perturbation is periodic and the response is linear (Chernyshov et al, 2011). In practice, an approach called phase-sensitive detection (PSD) has been applied for analysis of diffraction data (Caliandro et al, , 2013Ferri et al, 2014;Lu et al, 2014). In terms of Fourier harmonics A 2Â ½n considered above, it assumes the following integral transformation:…”
Section: Discussionmentioning
confidence: 99%
“…MED can also serve as a tool that helps to untangle the interference contribution in the detected intensity and, therefore, provides partial information on phases of complex structural amplitudes. So far, a quantitative analysis of frequency spectra of the diffraction response is limited to the Bragg intensities and is only focused on the second harmonics, whereas some promising applications of MED for powder diffraction show a strong and interesting response on the first harmonic Lu et al, 2014). There are no mathematical formulae that could be used to quantify the response for realistic conditions when both structure factors and unit-cell dimensions are varied; this is why many interesting observations are doomed to be discussed only qualitatively.…”
Section: Introductionmentioning
confidence: 99%
“…Ar ecent articler eported that support phase transformation and particle sintering were found after thermal (at 900 8Ci na ir) and stoichiometric( at 900 8C, air/fuel equivalent ratio = 1) aging over aP d/YFeO 3 three-way catalyst. [104] Them echanism of catalyst deactivation has been recently investigated under simulated VA Mg as conditions,i np articular. [88] Catalyst deactivation is initially caused by palladium particle migration, followed by particle growth, and changes in support structure.T his is more prominent in the presence of water vapor.…”
Section: Palladium-based Catalystsmentioning
confidence: 99%